Parasite–gut microbiota associations in wild wood mice (Apodemus sylvaticus) - Marsh, Kirsty J.; Raulo, Aura R.; Webster, Joanne P.; Knowles, Sarah C. L. (Frontiers in Microbiology, 2024)
The mammalian gastrointestinal tract provides a habitat for multiple commensal and pathogenic organisms spanning all three domains of life. Both positive and negative interactions to occur between gut inhabitants, with potential consequences for host health. Studies of parasite-microbiota associations in natural systems remain scarce, yet are important for understanding how parasite 2 communities and commensal microbiota shape each other, and how these interactions influence host health. Here, we characterise associations between helminth and coccidial infections and gut microbiota profiles in a wild population of wood mice (Apodemus sylvaticus) over three years, using two complimentary approaches. We first examined parasite-microbiota associations along the length of the gastrointestinal tract through destructive sampling. Then, in a larger non-invasive capture markrecapture study we assessed whether gut parasitic infections detected in faeces predicted faecal microbiota diversity and composition. We found that while overall microbiota composition was not associated with infection by any common gut parasite species, microbiota richness was associated with gut parasitism in two ways: (i) Infection by the trematode Corrigia vitta in the small intestine predicted higher microbiota diversity in the caecum; (ii) There was a negative relationship between gut parasite richness and faecal microbiota richness in the non-invasive study. As our results identified associations between gastrointestinal parasites and microbiota alpha diversity, future experimental work in this tractable wild mammalian system would be valuable to definitively test the directionality of these interactions.